The Fagerström and AUDIT Tests as Probable Screening Tools in Oral Cancer and Their Correlation with CYP1A1, GSTM1, GSTP1, and GSTT1 Gene Expression - Bandeira, Celso Muller [UNESP]; Almeida, Adriana Ávila [UNESP]; Alves, Mônica Ghislaine Oliveira; Pascoal, Maria Beatriz Nogueira; Chagas, José Francisco Sales; Neto, Morun Bernardino; de Barros, Patrícia Pimentel [UNESP]; Nunes, Fábio Daumas; Carta, Celina Faig Lima [UNESP]; Almeida, Janete Dias [UNESP] (MDPI, 2022)
Background: Cancer is currently a major public health problem worldwide, with a marked increase of about 70% in the number of expected diagnosed cases over the next two decades. The amount of tobacco and alcohol consumed is calculated based on the subjective information provided by the user. Tobacco exposure can be assessed using the Fagerström Test for Cigarette Dependence (FTCD) and alcohol consumption by the Alcohol Use Disorder Identification Test (AUDIT). Materials and Methods: Forty-eight subjects answered the Fagerström, and AUDIT tests and we studied them as likely screening tools for oral cancer and their correlation with the expression of CYP1A1, GSTM1, GSTP1, and GSTT1 genes by the RT-qPCR method. Results: There were significant differences in the AUDIT score and CYP1A1 expression between cancer and control groups. Participants in advanced stages, whether due to tumor size or regional metastasis, showed significant differences in the duration of tobacco use, FTCD, AUDIT score, and CYP1A1 expression when compared to patients in early stages. Among subjects without cancer, we found a significant correlation between participant age and GSTP1 expression. Furthermore, the expression of GSTP1 was significantly correlated with the number of cigarettes smoked per day, duration of tobacco use, and FTCD. Conclusions: Questionnaires designed to evaluate the degree of tobacco and alcohol exposure and dependence combined with gene expression tests can be useful to assess the risk of developing oral cancer. Furthermore, raising the awareness of individuals regarding their degree of dependence and encouraging them to participate in cessation programs are important educational measures for the prevention of tobacco-related malignancies.
Keywords: buccal mucosa; carcinogenesis; gene expression; mouth neoplasms; squamous cell carcinoma; xenobiotic